Understanding the CISG a compact guide to the 1980 United Nations Convention on Contracts for the International Sale of Goods - Lookofsky, Joseph M. (Kluwer Law International B.V., 2017)
Understanding the CISG' draws upon the full range of primary and secondary sources of the United Nations Convention on Contracts for the International Sale of Goods (CISG) law, including worldwide case law and scholarly opinion in this fully updated fifth (worldwide) edition. The 1980 CISG regulates the rights of buyers and sellers in international sales. The Convention is the first sales law treaty to win acceptance on a worldwide scale, and the impressive list of some eighty-five CISG?Contracting States? already accounts for more than three-fourths of all world trade. The importance of the CISG in the international arena is underlined by thousands of reported decisions where the CISG has been held to apply, thus evidencing the conduct of countless international traders who? by default or by express choice? regularly subject their sales contracts to the Convention. The CISG has also impacted on sales legislation at national and regional (e.g., EU) levels.